2018
DOI: 10.1029/2018jd028418
|View full text |Cite
|
Sign up to set email alerts
|

An Extreme Rainfall Event in Coastal South China During SCMREX‐2014: Formation and Roles of Rainband and Echo Trainings

Abstract: In this study, an extreme rainfall event of 451 mm in 20 hr that occurred in coastal South China on 11 May 2014 during the Southern China Monsoon Rainfall Experiment is investigated using integrated observations from the dual‐Doppler radar pair, polarimetric radar, extensive mesonetwork, and enhanced upper‐air soundings. Results show the generation of the extreme rainfall by two consecutive mesoscale convective systems (MCSs) consisting of multiple meso‐β‐scale rainbands. The two MCSs are maintained by lifting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 57 publications
4
56
0
Order By: Relevance
“…2). These statistics further supplement those of previous case studies that found existence of dual rain belts over coastal and inland SC during the pre-summer rainy season (Huang et al 1986;Ding 1994;Du and Chen 2018;Liu et al 2018). The presence and structure of LLJs are analyzed using ERA-interim data, largely following the methods adopted by Du et al (2014) to reveal their possible relation with the pre-summer rainfall over the SC coast.…”
Section: Analysis Of the Synoptic Conditionssupporting
confidence: 61%
“…2). These statistics further supplement those of previous case studies that found existence of dual rain belts over coastal and inland SC during the pre-summer rainy season (Huang et al 1986;Ding 1994;Du and Chen 2018;Liu et al 2018). The presence and structure of LLJs are analyzed using ERA-interim data, largely following the methods adopted by Du et al (2014) to reveal their possible relation with the pre-summer rainfall over the SC coast.…”
Section: Analysis Of the Synoptic Conditionssupporting
confidence: 61%
“…The impact of low-level warm and humid flow (e.g., Huang et al, 1986;Wang, Luo, et al, 2014), land-sea effects (e.g., Chen et al, 2014;Wu et al, 2017), terrain effects (e.g., Wu & Luo, 2016;Xu et al, 2012), and convective environmental conditions of mesoscale convective systems (MCSs; e.g., Xia et al, 2006;Zhang et al, 2011) have been emphasized. In recent years, using smaller spacing mesoscale observation data, several observation-based analyses have examined the structure, initiation, maintenance, and properties of warm-sector torrential rainfallassociated MCSs (e.g., Wang, Luo, et al, 2014;Wu & Luo, 2016;Liu et al, 2018). Planetary boundary layer (PBL) weather systems such as low-level jets, near-surface winds, and precipitation-generated cold outflows have been demonstrated to play important roles in initiating and maintaining warm-sector rainfall (Chen et al, 2017;Du & Chen, 2019;Wang, Luo, et al, 2014;Wu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Organized mesoscale convective systems (MCSs) are regarded as a main contributor to heavy rainfall during the rainy season (Kuo & Chen, ; Luo et al, ; Zhang et al, ). Heavy rainfall and relevant MCSs during the presummer rainy season can be influenced by complicated multiscale atmospheric processes, including synoptic or subsynoptic weather systems (Huang et al, ; Kuo & Chen, ; Luo et al, ; Zhang et al, ; Zhang & Meng, ), local forcings such as terrain effects (Wang, Luo & Jou., ), land‐sea breezes (Chen et al, ; Chen et al, ), boundary layer winds or jets (Du & Chen, ), convectively generated cold pools (Liu et al, ; Wu & Luo, ), and urban heat islands (Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%